An experimental study on optimization of SiO2/water nanofluid flows in circular minichannels - Subasi, Abdussamet; Manay, Eyuphan; Elbas, Seyma; Sahin, Bayram (SPRINGER, 2021)
An experimental research was performed to examine the effect of hydrodynamically and thermally developing distilled water-based SiO2 nanofluid flows in circular minichannels subject to constant heat flux boundary condition on the hydro-thermal performance. The Reynolds number (Re), the diameter of minichannel (D), and the nanoparticle volume concentration of (phi) were considered as design and flow parameters. As objective functions, the Nusselt number (Nu) and the friction factor (f) were determined. Each design parameter was investigated in three levels as 300, 600, and 900 for Re, 1.21, 1.55, and 1.90 mm for D and 0, 0.4%, and 0.8% for phi. The properties of the distilled water and the synthesized nanofluids which were required in heat transfer and fluid flow calculations were experimentally determined as a function of temperature between 20 and 60 degrees C. The objective functions were mathematically represented in terms of the design and flow parameters using the Response Surface Methodology. The effectiveness of these meta-models was tested both experimentally and statistically. The effect of each parameter on Nu and f were investigated in detail. Finally, as a result of a multi-objective optimization analysis, the optimum design and flow parameters were reported as a Pareto solution set that maximizes Nu and minimizes f simultaneously.
Keywords: Nanofluid; SiO2; Minichannel; Heat transfer; Response surface methodology; Multi-objective optimization; HEAT-TRANSFER ENHANCEMENT; PRESSURE-DROP; MULTIOBJECTIVE OPTIMIZATION; AL2O3/WATER NANOFLUID; THERMAL-CONDUCTIVITY; HYBRID NANOFLUID; BROWNIAN-MOTION; LIQUID FLOW; SINK; PERFORMANCE; Thermodynamics; Chemistry